2018
DOI: 10.1002/cctc.201701422
|View full text |Cite
|
Sign up to set email alerts
|

Internal Donors in Ziegler–Natta Systems: is Reduction by AlR3 a Requirement for Donor Clean‐Up?

Abstract: Alkyl benzoates, phthalates, and succinates are used as “internal donors” (ID) to modify the surface of MgCl2‐supported Ziegler–Natta (ZN) catalysts for polypropylene production. Phthalates, in particular, are the working horses of this catalysis, but a REACH ban of these compounds for other applications has generated a desire from the market for phthalate‐free ZN catalysts, which has in turn triggered a search for alternatives and revamped research in the area. It has been reported that under polymerization c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…The computational protocol M06-2X/TZ(PCM)//TPSSTPSS/DZ has been previously benchmarked 56 , 57 and widely used for modeling of Al-species relevant to olefin polymerization 33 , 44 , 58 , 59 and other research fields, 60 and it has been shown to be suitable for studies related to MAO activators. 19 , 33 , 35 , 41 , 51 , 61 Additional inclusion of Grimme-type long-range dispersion corrections 62 , 63 does not affect computational results significantly (see Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…The computational protocol M06-2X/TZ(PCM)//TPSSTPSS/DZ has been previously benchmarked 56 , 57 and widely used for modeling of Al-species relevant to olefin polymerization 33 , 44 , 58 , 59 and other research fields, 60 and it has been shown to be suitable for studies related to MAO activators. 19 , 33 , 35 , 41 , 51 , 61 Additional inclusion of Grimme-type long-range dispersion corrections 62 , 63 does not affect computational results significantly (see Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…Final single‐point energies were calculated at the M06‐2X level of theory employing triple‐ζ Dunning (TZ) basis sets (cc‐pVTZ quality) . This level of theory has proven suitable for studies related to MAO, , , , and other Al‐alkyl compounds , . Enthalpies and Gibbs free energies were then obtained from TZ single‐point energies and thermal corrections from the TPSSTPSS/cc‐pVDZ‐(PP) vibrational analyses; entropy corrections were scaled by a factor of 0.67 to account for decreased entropy in the condensed phase .…”
Section: Methodsmentioning
confidence: 99%
“…[84] This level of theory has proven suitable for studies related to MAO [7,29,50,56,92] and other Al-alkyl compounds. [38,[93][94][95] Enthalpies and Gibbs free energies were then obtained from TZ single-point energies and thermal corrections from the TPSSTPSS/cc-pVDZ-(PP) vibrational analyses; entropy corrections were scaled by a factor of 0.67 to account for decreased entropy in the condensed phase. [96][97][98] A model cluster for MAO cages, proposed by Zurek and co-workers, [6,99] was used.…”
Section: Esi-ms Experimentsmentioning
confidence: 99%
“…Solvent influence (toluene, ϵ =2.3741) was modeled explicitly, using the polarizable continuum model (PCM) implemented in the Gaussian 09 software suite. The M06‐2X functional has been shown to yield accurate results for systems involving aluminum systems …”
Section: Methodsmentioning
confidence: 99%